Analisis Yuridis Perilaku Lesbian dari Seorang Isteri sebagai Alasan Perceraian - Siregar, Lita Mardani (Mahesa Research Center, 2019)
One of the principles in national marriage law that is in line with religious teachings is to make divorce difficult (divorce), because divorce means the failure of the purpose of marriage to form a happy and eternal family due to human actions. The problem in this reshearch is how is the regulation of the implementation of divorce in the Religious Court, what is the effect of the divorce law on the grounds of lesbian behavior of a wife, how is the consideration of the judge in the Ambon Religious Court decisionNumber 110 / Pdt.G / 2016 / PA Ab. As a result of divorce law on the grounds that the lesbian behavior of a wife is related to child custody. The legal effect on marital property is that joint property is divided according to the provisions of the respective laws, laws, religion and customary law, while the inheritance remains controlled by each of the wives and divorced husbands. With regard to debt due to termination of marriage due to divorce borne by both parties with conditions that must be met where the rights and obligations of husband and wife are balanced in their authority to carry out legal actions. Judge's consideration in the decision of the Ambon Religious Court Number 110 / Pdt.G / 2016 / PA Ab in the case of sexual disorders (lesbians) immediately considers that this is in accordance with the provisions in Article 39 paragraph 2 of Law Number 1 of 1974 along with the explanation in letter e and letter f juncto Article 19 letter f Government Regulation Number 9 of 1975, Article 116 letter e and letter f Inpres No. 1 of 1991 concerning the Compilation of Islamic Law (KHI).